Serum creatinine to cystatin C ratio and cognitive function among middle-aged and older adults in China - Zhu, Yueli; Tan, Zhongju; Li, Shumin; Zhu, Feng; Qin, Chengfan; Zhang, Qin; Yang, Yunmei (Frontiers in Aging Neuroscience, 2022)
Background The sarcopenia index (SI, serum creatinine / serum cystatin C × 100) is recently suggested to be a reliable marker for sarcopenia. It has been reported that sarcopenia is associated with poorer cognition. The purpose of this study was to evaluate the association between SI and cognitive function among middle-aged and older adults from the China Health and Retirement Longitudinal Study (CHARLS). Methods 6442 participants ≥ 45 years of age were enrolled in this study from CHARLS between 2011 and 2012. Cognitive function was assessed by interview-based measurements, including orientation and attention, episodic memory, visuo-construction, and the total cognitive function. SI was calculated by serum creatinine (mg/dL) / cystatin C (mg/L) × 100. One-way analysis of variance (ANOVA) was used to compare the differences among groups divided according to SI quartiles by gender. Both linear and logistic regression models were applied to investigate the relationship between SI and cognitive function. Results After adjustment for potential confounders, we found SI was significantly and positively correlated with total cognitive function scores both in males and females [β = 0.014, 95% confidence interval (CI) 0.007 to 0.021, P < 0.001; β = 0.011, 95 CI% 0.003 to 0.018, P = 0.004; respectively]. Similarly, when the total cognitive function score was treated as a categorical variable according to quartiles in males and females, higher SI was related to better total cognitive function scores in both males and females [odds ratio (OR) =1.147, 95% CI 1.028 to 1.279, P = 0.014; OR = 1.219, 95% CI 1.106 to 1.344, P < 0.001; respectively] following adjustment for confounders. Conclusions SI was correlated with the prevalence of cognitive impairment among middle-aged and older adults in China.